Risk Management in Insurance Companies - Yang, Xufeng (2006)
Insurance is the uncertain business in uncertain society. Today, insures face more complex and difficult risks. Efficient risk management mechanisms are essential for the insurers. The paper is set out initially to explore UK insurance companies risk management and risk disclosure by examining companies annual report after all the listed insurance companies are required to disclose risk information in their annual report, which seeks to reflect the recent development in UK insurance companies practices on risk management and risk disclosure. In particular, the author sought to understand: companies compliance with IFRS 4 on the requirement of risk disclosure; the rationale of companies risk management practice; the development of risk management in terms of risk management function improvement and risk management process development; and how all these issues are influenced by a companys nature. The main findings are regulators requirements could have a significant effect, and companies risk management and risk disclosure subject to their nature.